2023
DOI: 10.3390/fermentation9030231
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fermented Dairy Products on Gut Microbiota Composition

Abstract: Milk and dairy products are among the most important foods in the human diet. They are natural and culturally accepted and supply the human body with microorganisms that modulate the intestinal microflora. Improper lifestyles, highly processed diets, and certain drugs may contribute to adverse changes in the composition of the gut microflora. These changes may lead to dysbiosis, which is associated with the pathogenesis of many gastrointestinal diseases. This review aims to determine the effect of fermented mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Pediatricians practicing in rural/semi-urban areas recommend the earlier introduction of local dairy products, such as ariani—a fermentation product known to benefit the gut microflora and the immune system [ 46 ]. This group of pediatricians also recommends the early introduction of meat from domestic animals, such as rabbit, and game meat, as well as sesame, tree nuts, seafood, legumes and tomato, probably because of their local availability [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pediatricians practicing in rural/semi-urban areas recommend the earlier introduction of local dairy products, such as ariani—a fermentation product known to benefit the gut microflora and the immune system [ 46 ]. This group of pediatricians also recommends the early introduction of meat from domestic animals, such as rabbit, and game meat, as well as sesame, tree nuts, seafood, legumes and tomato, probably because of their local availability [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The various health benefits of yogurt, cheese, kefir, and other traditional fermented milk products have been extensively researched. Probiotic strains of bacteria present in fermented dairy products are beneficial for gut health and can reduce the risk of certain diseases (Okoniewski et al 2023 ). Additionally, fermented dairy products are a rich source of vitamins and minerals, including calcium, potassium, phosphorus, and B vitamins.…”
Section: Fermented Dairy Productsmentioning
confidence: 99%
“…Typically, these starters consist of complex microbial communities, including various species of lactobacilli and proteobacteria. Numerous studies [3][4][5] have confirmed that consuming traditional fermented dairy products with probiotic cultures positively affects the gut microbiota and human immunity. For instance, Jing Li et al showed that the predominant taxa in Kazakh artisanal cheeses are Lactococcus lactis (28.93%), Lactobacillus helveticus (26.43%), Streptococcus thermophilus (12.18%), and Lactobacillus delbrueckii (12.15%) [6].…”
Section: Introductionmentioning
confidence: 99%